Perancangan Sistem Pengelolaan Engineering Order pada Lini Produksi - Yatna Yuwana Martawirya; Syfa Nur’aini Septianingsih; Suryandaru Martawirya (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
Production line is a place for production activities that consists series of workstations. The product moves from one workstation to the next in sequence to go through the stages of the process. Products are composed of components, sub-assemblies, or assemblies. During production activities, it is possible to change materials which are part of a product structure. This happened because of the proposal from the company staff which is submitted through an engineering order. Submissions are made for technical reasons or production costs. The decision to approve or reject the engineering order is determined by designer. The approved engineering order resulted in changes to the product structure and material requirements at the workstation where the material was changed. The process for handling new materials can also change depending on the designer's decision whether to use the old or new process. It is necessary to determine whether the old process is still used or not if designer decides to use a new process. Therefore, a system is needed to manage engineering orders so that changes can be updated automatically. The engineering order management system media is a web-based application. It is vital to model the system based on real-world situations before designing a web application. The object-oriented modeling concept, which is expressed in a class diagram, is used to model the system. Web development using the Python programming language and the Django framework has been carried out successfully. Every web feature has worked as expected.